Sikap Kritis terhadap Kekuasaan dalam Tradisi Calvinist: Sebuah Kajian Historis-Teologis Tentang Kekritisan Gereja terhadap Pemerintah untuk Mewujudkan Regnum Christi: Critical Attitude Toward The State In Calvinist Tradition: A Historical Discourse About Church Criticism To The Goverment To Build Regnum Christi - Suarbudaya Rahadian; Fially Fallderama (Societas Dei: Jurnal Agama dan Masyarakat, 2020)
Protestant political theology believes the government is God’s vice in this world therefore has a legitimation to manage all aspect of human life. This conviction affected Protestants to unquestioningly obeyed the goverment. On the other hand the doctrine of the fall in Reformed tradition, believes that all aspect of creation has fall short of glory, consequently, the government as a part of creation could also fell into corruption. For this reason, a long-standing of Calvinist tradition has a lot of theological resourcement to be critical-constructive to authority. This paper tries to dig John Calvin’s theological treatises from his early writing and seminal works through historical theology method, to find Calvin’s basic idea about the critical nature of church-goverment relationship. The excavation from Calvin’s early writing in this paper prospecfully would give critical and analytical tools to undertand ethical relation between church and government in Indonesia context. Keywords:political theology; calvinism; historical theology; critical attitude; government.